2017
DOI: 10.1074/jbc.m117.799940
|View full text |Cite
|
Sign up to set email alerts
|

Protonation-dependent stepped rotation of the F-type ATP synthase c-ring observed by single-molecule measurements

Abstract: The two opposed rotary molecular motors of the FF-ATP synthase work together to provide the majority of ATP in biological organisms. Rotation occurs in 120° power strokes separated by dwells when F synthesizes or hydrolyzes ATP. F and F complexes connect via a central rotor stalk and a peripheral stator stalk. A major unresolved question is the mechanism in which the interaction between subunit-a and rotating subunit-c-ring in the F motor uses the flux of H across the membrane to induce clockwise rotation agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 28 publications
(38 reference statements)
4
53
0
Order By: Relevance
“…A recent single-molecule study of F 1 F o reported forward and backward stepping of the rotor by ~30°, i.e. up to one c-subunit (18). However, with F 1 anchored to the support by subunit b and a probe attached to c, flexibility at OSCP would not be detected.…”
Section: Rotary Substates Reveal Concerted Rotation Of F 1 and Centramentioning
confidence: 93%
See 1 more Smart Citation
“…A recent single-molecule study of F 1 F o reported forward and backward stepping of the rotor by ~30°, i.e. up to one c-subunit (18). However, with F 1 anchored to the support by subunit b and a probe attached to c, flexibility at OSCP would not be detected.…”
Section: Rotary Substates Reveal Concerted Rotation Of F 1 and Centramentioning
confidence: 93%
“…Studies aiming to characterize flexible coupling have focused on the central stalk (17), often working with an F 1 and rotor subcomplex. When the whole F 1 F o complex was examined, it was nonetheless normally attached to substrate and reporter molecules at subunits b and c to probe for flexibility along the F 1 -F o axis (9,18,19). A recent single-molecule study of F 1 F o reported forward and backward stepping of the rotor by ~30°, i.e.…”
Section: Rotary Substates Reveal Concerted Rotation Of F 1 and Centramentioning
confidence: 99%
“…Studies aiming to characterize flexible coupling have focused on the central stalk (21), often working with an F 1 and rotor subcomplex. When the whole F 1 F o complex was examined, it was typically attached to substrate and reporter molecules at subunits b and c to probe for flexibility along the F 1 -F o axis (9,22,23). A recent singlemolecule study of F 1 F o reported forward and backward stepping of the rotor by~30°(i.e., up to one c subunit) (22).…”
Section: High-resolution Map Of a Complete F-type Atp Synthase Dimermentioning
confidence: 99%
“…When the whole F 1 F o complex was examined, it was typically attached to substrate and reporter molecules at subunits b and c to probe for flexibility along the F 1 -F o axis (9,22,23). A recent singlemolecule study of F 1 F o reported forward and backward stepping of the rotor by~30°(i.e., up to one c subunit) (22). However, with F 1 anchored to the support by subunit b and a probe attached 4 of 10 to c, flexibility at OSCP would not be detected.…”
Section: High-resolution Map Of a Complete F-type Atp Synthase Dimermentioning
confidence: 99%
“…When viewed from the membrane side, the two half-channels are asymmetrically arranged: the right semi-channel turns towards the P-side of the membrane, while the left semi-channel faces the N-side, to ensure obliged proton translocation into one direction only that is linked to the rotation of the central stalk and the catalysis reaction in F 1 [106,107]. Recent experiments have shown that access to the two half-channels is not the same from both sides of the membrane [108].…”
Section: Asymmetric Elements In the F-atp Synthasementioning
confidence: 99%